2017
DOI: 10.1136/openhrt-2017-000658
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of risk for sudden death in childhood hypertrophic cardiomyopathy: the importance of the ECG risk score

Abstract: ObjectiveTo establish which risk factors are predictive for sudden death in hypertrophic cardiomyopathy (HCM) diagnosed in childhood.MethodsA Swedish national cohort of patients with HCM diagnosed <19 years of age was collected between 1972 and 2014, consisting of 155 patients with available ECGs, with average follow-up of 10.9±(SD 9.0) years, out of whom 32 had suffered sudden death or cardiac arrest (SD/CA group). Previously proposed risk factors and clinical features, ECG and ultrasound measures were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(89 citation statements)
references
References 31 publications
3
84
0
2
Order By: Relevance
“…The presence of long QTc is found in about 12% of HCM patients [ 17 ] and it is considered a predictor for the need of ICD (Implantable Cardioverter-Defibrillator) implantation. The QTc length risk in HCM was also a feature noted by other groups [ 18 , 19 ]. Concerning the cause of QTc abnormalities in HCM, either a structural or a genetic origin could be hypothesized.…”
Section: Discussionsupporting
confidence: 64%
“…The presence of long QTc is found in about 12% of HCM patients [ 17 ] and it is considered a predictor for the need of ICD (Implantable Cardioverter-Defibrillator) implantation. The QTc length risk in HCM was also a feature noted by other groups [ 18 , 19 ]. Concerning the cause of QTc abnormalities in HCM, either a structural or a genetic origin could be hypothesized.…”
Section: Discussionsupporting
confidence: 64%
“…Beta-blocker therapy reduces LVOT gradient in HOCM, both at rest and during exercise, and improves symptoms, diastolic function and exercise capacity 16–21. In childhood HCM, it is also associated with improved survival22 in a dose-related manner,23 24 and reduces risk of SCD 25. It has been claimed that beta-blocker therapy does not affect survival in adult HCM,26 although Frank et al 27 reported particularly low SCD mortality (0.3%) in patients treated with relatively high doses of propranolol, aiming for ≥320 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomised trial in non-obstructive HCM has not been performed. The observation that it takes around 5 years for survival curves to diverge significantly (figure 1A) indicates that the effect may be particularly on myocardial preservation perhaps affecting progress of fibrosis, rather than reducing SCD mortality as reported with higher paediatric dosages 25. Lacking controlled trials, it would be desirable that large international registries for HCM should collect and publish data on mortality related to pharmacotherapy, both type and dose.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты крупного научного исследования, проведенного швейцарскими учеными, позволили установить, что смертность от ГКМП у детей в возрасте от 8 до 16 лет сопоставима с таковой у взрослых и составила 0,112 на 100000. Смертность у детей до 8 лет ми-нимальна и составляет 1,6%, затем увеличивается, достигая максимума к 10 годам -9,7% [15]. В структуре непосредственных причин смерти до 18% приходится на долю внезапной остановки сердца, которая может стать первым и единственным проявлением заболевания [15].…”
Section: гипертрофическая кардиомиопатияunclassified
“…Смертность у детей до 8 лет ми-нимальна и составляет 1,6%, затем увеличивается, достигая максимума к 10 годам -9,7% [15]. В структуре непосредственных причин смерти до 18% приходится на долю внезапной остановки сердца, которая может стать первым и единственным проявлением заболевания [15].…”
Section: гипертрофическая кардиомиопатияunclassified